Current measurements in the intermittent-contact mode of atomic force microscopy using the Fourier method: a feasibility analysis - Uluutku, Berkin; Solares, Santiago D. (Beilstein Journal of Nanotechnology, 2020)
Atomic force microscopy (AFM) is an important tool for measuring a variety of nanoscale surface properties, such as topography, viscoelasticity, electrical potential and conductivity. Some of these properties are measured using contact methods (static contact or intermittent contact), while others are measured using noncontact methods. Some properties can be measured using different approaches. Conductivity, in particular, is mapped using the contact-mode method. However, this modality can be destructive to delicate samples, since it involves continuously dragging the cantilever tip on the surface during the raster scan, while a constant tip–sample force is applied. In this paper we discuss a possible approach to develop an intermittent-contact conductive AFM mode based on Fourier analysis, whereby the measured current response consists of higher harmonics of the cantilever oscillation frequency. Such an approach may enable the characterization of soft samples with less damage than contact-mode imaging. To explore its feasibility, we derive the analytical form of the tip–sample current that would be obtained for attractive (noncontact) and repulsive (intermittent-contact) dynamic AFM characterization, and compare it with results obtained from numerical simulations. Although significant instrumentation challenges are anticipated, the modelling results are promising and suggest that Fourier-based higher-harmonics current measurement may enable the development of a reliable intermittent-contact conductive AFM method.
Keywords: atomic force microscopy (AFM); conductivity; current; intermittent contact; Fourier analysis; tapping-mode AFM

(untitled) - Noh, H.; Diaz, A. J.; Solares, S. D. (Beilstein J. Nanotechnol., 2017)

(untitled) - O’Dea, J. R.; Brown, L. M.; Hoepker, N.; Marohn, J. A.; Sadewasser, S. (MRS Bull., 2012)

(untitled) - Pingree, L. S. C.; Reid, O. G.; Ginger, D. S. (Adv. Mater. (Weinheim, Ger.), 2009)

(untitled) - Pingree, L. S. C.; Reid, O. G.; Ginger, D. S. (Nano Lett., 2009)

(untitled) - Reid, O. G.; Munechika, K.; Ginger, D. S. (Nano Lett., 2008)

(untitled) - Kamkar, D. A.; Wang, M.; Wudl, F.; Nguyen, T.-Q. (ACS Nano, 2012)

(untitled) - Dante, M.; Peet, J.; Nguyen, T.-Q. (J. Phys. Chem. C, 2008)

2017 IEEE 24th International Symposium on the Physical and Failure Analysis of Integrated Circuits (IPFA) - Chen, Y. J.; Chan, S. C.; Liu, R.; Toh, S. L.; Ji, R. (Nano-electric studies on advanced semiconductor devices by conductive AFM, 2017)

(untitled) - Trenkler, T. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 1998)

(untitled) - Olbrich, A.; Ebersberger, B.; Boit, C. (Appl. Phys. Lett., 1998)

(untitled) - Farha Al-Said, S. A.; Hassanien, R.; Hannant, J.; Galindo, M. A.; Pruneanu, S.; Pike, A. R.; Houlton, A.; Horrocks, B. R. (Electrochem. Commun., 2009)

(untitled) - Li, L. H.; Xing, T.; Chen, Y.; Jones, R. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Beinik, I.; Kratzer, M.; Wachauer, A.; Wang, L.; Piryatinski, Y. P.; Brauer, G.; Chen, X. Y.; Hsu, Y. F.; Djurišić, A. B.; Teichert, C. (Beilstein J. Nanotechnol., 2013)

(untitled) - Zhong, Q.; Inniss, D.; Kjoller, K.; Elings, V. B. (Surf. Sci. Lett., 1993)

(untitled) - Alexeev, A.; Loos, J.; Koetse, M. M. (Ultramicroscopy, 2006)

(untitled) - Vuppu, A. K.; Garcia, A. A.; Vernia, C. (Biopolymers, 1997)

(untitled) - Farina, M.; Ye, T.; Lanzani, G.; di Donato, A.; Venanzoni, G.; Mencarelli, D.; Pietrangelo, T.; Morini, A.; Keivanidis, P. E. (Nat. Commun., 2013)

(untitled) - Jiang, G.; Baba, A.; Advincula, R. (Langmuir, 2007)

Nano Optoelectronic Sensors and Devices - Liu, L.; Xi, N.; Li, G.; Chen, H. (Atomic Force Microscope-Based Nanorobotic System for Nanoassembly, 2012)

(untitled) - Moreno-Herrero, F.; Colchero, J.; Gómez-Herrero, J.; Baró, A. M. (Phys. Rev. E, 2004)

Roadmap of Scanning Probe Microscopy - Morita, S. (Springer Berlin, 2007)

(untitled) - Fein, A.; Zhao, Y.; Peterson, C. A.; Jabbour, G. E.; Sarid, D. (Appl. Phys. Lett., 2001)

(untitled) - Vecchiola, A.; Chrétien, P.; Delprat, S.; Bouzehouane, K.; Schneegans, O.; Seneor, P.; Mattana, R.; Tatay, S.; Geffroy, B.; Bonnassieux, Y.; Mencaraglia, D.; Houzé, F. (Appl. Phys. Lett., 2016)

(untitled) - Garcia, R.; Proksch, R. (Eur. Polym. J., 2013)

(untitled) - Kawai, S.; Glatzel, T.; Koch, S.; Such, B.; Baratoff, A.; Meyer, E. (Phys. Rev. B, 2010)

(untitled) - Garcia, R.; Herruzo, E. T. (Nat. Nanotechnol., 2012)

(untitled) - Stark, M.; Stark, R. W.; Heckl, W. M.; Guckenberger, R. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Sahin, O.; Magonov, S.; Su, C.; Quate, C. F.; Solgaard, O. (Nat. Nanotechnol., 2007)

(untitled) - Solares, S. D.; Hölscher, H. (Nanotechnology, 2010)

(untitled) - Tholén, E. A.; Platz, D.; Forchheimer, D.; Schuler, V.; Tholén, M. O.; Hutter, C.; Haviland, D. B. (Rev. Sci. Instrum., 2011)

(untitled) - Platz, D.; Tholén, E. A.; Pesen, D.; Haviland, D. B. (Appl. Phys. Lett., 2008)

(untitled) - Borgani, R.; Gilzad Kohan, M.; Vomiero, A.; Haviland, D. B. (Phys. Rev. Appl., 2019)

Handbook of Mathematical Functions with Formulas, Graphs, and Mathematical Tables - Abramowitz, M.; Stegun, I. A. (Dover Publications Inc., 1965)

(untitled) - Dürig, U. (Appl. Phys. Lett., 1999)

(untitled) - Dürig, U. (Surf. Interface Anal., 1999)

(untitled) - Dürig, U. (New J. Phys., 2000)

(untitled) - Hembacher, S.; Giessibl, F. J.; Mannhart, J. (Science, 2004)

(untitled) - Giessibl, F. J. (Surf. Interface Anal., 2006)

(untitled) - Wright, C. A.; Solares, S. D. (Appl. Phys. Lett., 2012)

(untitled) - Santos, S.; Barcons, V.; Font, J.; Verdaguer, A. (Beilstein J. Nanotechnol., 2014)

(untitled) - Stark, R. W.; Heckl, W. M. (Rev. Sci. Instrum., 2003)

Intermolecular and Surface Forces - Israelachvili, J. (Academic Press, 2011)

The Scientist & Engineer’s Guide to Digital Signal Processing - Smith, S. W. (California Technical Publishing, 1997)

(untitled) - Tamayo, J.; García, R. (Langmuir, 1996)

(untitled) - García, R.; Pérez, R. (Surf. Sci. Rep., 2002)

(untitled) - Leite, F. L.; Bueno, C. C.; Da Róz, A. L.; Ziemath, E. C.; Oliveira, O. N., Jr (Int. J. Mol. Sci., 2012)

(untitled) - Solares, S. D.; An, S.; Long, C. J. (Beilstein J. Nanotechnol., 2014)

Variable Gain High Speed Current Amplifier DHPCA-100 - FEMTO® Messtechnik GmbH

(untitled) - Kemiktarak, U.; Ndukum, T.; Schwab, K. C.; Ekinci, K. L. (Nature, 2007)

(untitled) - Manassen, Y.; Hamers, R. J.; Demuth, J. E.; Castellano, A. J., Jr (Phys. Rev. Lett., 1989)

(untitled) - Legleiter, J.; Park, M.; Cusick, B.; Kowalewski, T. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Člupek, M.; Matějka, P.; Volka, K. (J. Raman Spectrosc., 2007)

(untitled) - Barton, S. J.; Ward, T. E.; Hennelly, B. M. (Anal. Methods, 2018)

(untitled) - Chen, H.; Xu, W.; Broderick, N.; Han, J. (J. Raman Spectrosc., 2018)

(untitled) - Chen, B.; Yang, M.; Priya, S.; Zhu, K. (J. Phys. Chem. Lett., 2016)

(untitled) - Yang, K. J.; Hu, C. (IEEE Trans. Electron Devices, 1999)

(untitled) - López-Guerra, E. A.; Eslami, B.; Solares, S. D. (J. Polym. Sci., Part B: Polym. Phys., 2017)

(untitled) - López-Guerra, E. A.; Solares, S. D. (Beilstein J. Nanotechnol., 2017)